Constituent Communication Through Telephone Town Halls: A Field Experiment Involving Members of Congress. Issue 4 (10th May 2019) - Abernathy, Claire; Esterling, Kevin M.; Freebourn, Justin; Kennedy, Ryan; Minozzi, William; Neblo, Michael A.; Solis, Jonathan A.
Abstract : Telephone town halls are an increasingly prevalent method for members of Congress (MCs) to communicate with constituents, even while garnering popular criticism for failing to facilitate engagement and accountability. Yet scholars have paid little attention to the events and their effects, and even less to how they might be improved. To remedy this problem, we report on a field experiment in which four MCs joined their constituents in telephone town halls. Overall, participation in an event improved constituents' evaluations of the format in general, and of the MC in particular. Furthermore, we studied how these events might be improved by evaluating a reform—a single‐topic focus with predistributed briefing materials—designed to enhance deliberative interaction. This reform enhanced effects on opinions of the format without significantly altering effects on attitudes toward the MC. Our results suggest that telephone town halls hold promise for constituents, officeholders, and democratic practice.